Pendampingan Manajemen Pemasaran Dalam Peningkatan Pelatihan Digital Marketing Dan Optimalisasi Media Sosial Batik Dan Tas Anyaman Talunombo - Leni Nur Khofifah; Trihudiyatmanto, M.; Efendi, Bahtiar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Talunombo Village products, such as batik and woven bags, have enormous potential but face challenges in terms of low competitiveness due to inadequate promotion through traditional methods and limited market reach. Previous approaches, such as direct marketing at local markets and exhibitions, failed to significantly increase sales due to limited customer access. To address this weakness, marketing management support was provided through innovative digital marketing training and social media optimization as a broader and more effective promotional tool. This article will explain the mentoring process and how it helped local businesses improve their promotional capabilities. The method used was a participatory strategy that included workshops, group discussions, and practical experience in producing digital materials. The program's results showed an 80% increase in business owners' understanding of digital marketing tactics, social media management skills, and ability to create content relevant to their target market. Furthermore, batik and woven bags expanded their promotional reach through digital channels, creating new marketing opportunities. Therefore, this assistance proved beneficial for the development of local creative businesses while supporting the economic independence of the Talunombo Village residents.